Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Sekretariat Daerah Kota Depok - Anggini Yuliastri Asih; Hamdi Supriadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of work discipline and work environment on employee performance at the Regional Secretariat of Depok City, both partially and simultaneously. The method used is quantitative. The results of the t test research showed that the calculated t for work discipline was 10.122 > t table of 1.988 or a significance of 0.00 < 0.05, meaning that partially there was a significant influence of work discipline on employee performance. And t calculated for the work environment is 9.052 > t table 1.988 or a significance of 0.00 < 0.50, meaning that partially there is a significant influence of the work environment on employee performance. For the f test, the calculated f is 80.881 > f table 2.71 or a significance of 0.00 < 0.50, meaning that simultaneously there is a significant influence of work discipline and work environment on employee performance. Multiple linear regression analysis obtained the equation Y = 4.360 + 0.537 (X1) + 0.364 (X2). The determination analysis obtained a value of 0.658 with a percentage of 65.8%, while the remaining 34.2% was caused by other variables.